Exhaled Nitric Oxide in Systemic Sclerosis Lung Disease - Natalie K. Kozij; John T. Granton; Philip E. Silkoff; John Thenganatt; Shobha Chakravorty; Sindhu R. Johnson (Canadian Respiratory Journal)
Background. Exhaled nitric oxide (eNO) is a potential biomarker to distinguish systemic sclerosis (SSc) associated pulmonary arterial hypertension (PAH) and interstitial lung disease (ILD). We evaluated the discriminative validity, feasibility, methods of eNO measurement, and magnitude of differences across lung diseases, disease-subsets (SSc, systemic lupus erythematosus), and healthy-controls. Methods. Consecutive subjects in the UHN Pulmonary Hypertension Programme were recruited. Exhaled nitric oxide was measured at 50 mL/s intervals using chemiluminescent detection. Alveolar and conducting airway NO were partitioned using a two-compartment model of axial diffusion (CMAD) and the trumpet model of axial diffusion (TMAD). Results. Sixty subjects were evaluated. Using the CMAD model, control subjects had lower median (IQR) alveolar NO than all PAH subjects (2.0 (1.5, 2.5) versus 3.14 ppb (2.3, 4.0), p=0.008). SSc-ILD had significantly lower median conducting airway NO compared to controls (1009.5 versus 1342.1 ml⁎ppb/s, p=0.04). SSc-PAH had increased median (IQR) alveolar NO compared to controls (3.3 (3.0, 5.7) versus 2.0 ppb (1.5, 2.5), p=0.01). SSc-PAH conducting airway NO inversely correlated with DLCO (r −0.88 (95% CI −0.99, −0.26)). Conclusion. We have demonstrated feasibility, identified that CMAD modeling is preferred in SSc, and reported the magnitude of differences across cases and controls. Our data supports discriminative validity of eNO in SSc lung disease.